An Analysis Types and Function of Swear Words Used in PewDiePie's Video - Ni Wayan Suastini; I Made Iwan Indrawan Jendra; Afrilya, Tini (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
Language is very important for every people, by using language people can communicate with each other in daily life. There are a lot of studies that discuss language and one of them is swear words. Swear words is a word or phrase that's generally considered blasphemous, vulgar, or otherwise offensive. These are also called bad words, obscenities, expletives, dirty words, profanities. The act of using a swear word is known as swearing. It can be divided into six types; Excretion, Death, Body Function Term, Religious Matter, Mother in Law and Sex Term. The article entitled "Analysis of the Types and Functions of Swear Words Used in the PewDiePie video, aims to identify the types of swearing in the PewDiePie video entitled" This is Bad. To analyze the data, the main theory used in this article is the theory of swear words proposed by Wardhaugh. This research used a descriptive qualitative method to present the data descriptively and qualitatively to support the data found in PewDiePie video. The results of the research on cursing found four types of curses, namely the term excretion, the term gender, the term body function, and the term death. In addition, the swear word function used in PewDiePie videos is primarily to express resentment, anger, and contempt for an object or subject while playing a game.